As relações interpessoais entre diretor e professores como fatores de mobilização do trabalho coletivo na escola - Cruz, Maria do Perpetuo Socorro (2016)
The objective of this study was to investigate how affection, with an emphasis on interpersonal relationships between the principal and teachers, affects the development of team work at the school, specifically how these relationships affect the pedagogical teaching and feelings of frustration/satisfaction and motivation/discouragement involving teaching in the school and also how they are perceived in the discourse of principals and teachers the effects of affection in interpersonal relationships. The functional domains are involved and for this reason, the research has as theoretical Henri Wallon whose theory is presented in Almeida and Mahoney studies. To achieve the result of this investigation, a principal took part in a semi-structured interview along with four teachers of public schools in São Paulo. The study pointed to the importance of interpersonal relationships among teachers and between them and the principal and his or her influence in teaching with the students. In this analysis, teachers, as well as the principal, expressed the importance of social interaction with colleagues for a better pedagogical performance. Some teachers of the state schools indicated interpersonal relationships as fundamental factor for good professional performance and teaching practice, as well as reported its impact on their pedagogical practice. Furthermore, our research pointed out the need for continuing education, not only for teachers in their specialties, but also for training aimed at the improvement of interpersonal relationships in order to develop an environment conducive to team work for both teachers and principals